Knowledge management for development : towards a practical approach for the Caribbean (ECLAC [Port of Spain]TT, 2009)
Proposes a framework for locating, collecting, creating, sharing and applying information and knowledge (from within and outside the subregion) for development purposes in the Caribbean subregion.
Keywords: ECONOMIC AND SOCIAL DEVELOPMENT